Advanced IoT Network Topologies to Optimize Medical Monitoring Platforms based on a Constrained and Secured IOT Application Protocol CoAP - Hamza Fatima Zahra; El Aidi Sanaa; Bajit Abderrahim; Beloualid Siham; Chaoui Habiba; Tamtaoui Ahmed (E3S Web of Conferences, 2022)
The Internet of Things (IoT) became, and still an important and critical element during the covid-19 pandemic, and this paper was written within that framework, as it proposes a synchronized medical IoT platform that is used to monitor citizens’ access to public areas, and where the access is only authorized if one of the three following conditions is fulfilled: Be vaccinated (which is verified via a QR code), having a negative PCR test (valid for only 48 hours), undergoing a body temperature measurement. Of course, a confirmation of identity with a facial recognition test is mandatory. This automatic process will allow us to reduce the possibility of spreading the disease due to the congestion of the checkpoints, as well as to detect citizens who could be potential patients of the covid-19 virus.